Leksell Gamma Knife® – The first 1000 patients from the radiation therapist's perspective. Issue 3 (9th October 2020) - Jenkins, Michael; Lusk, Ryan; Foley, Heath; Pinkham, Mark B; Olson, Sarah; Hall, Bruce; McBean, Angela; Jones, Catherine; Foote, Matthew
Abstract: The Princess Alexandra Hospital (PAH) Gamma Knife® Centre of Queensland (GKCoQ) began operations in October of 2015 as a sub‐specialty located within a larger radiation oncology service at PAH. It is uniquely positioned as the only Leksell Gamma Knife® (LGK) treatment unit available in the public hospital system in Australia, and the first and only service in Queensland. The GKCoQ treated the 1000th patient on 23 January 2019. LGK is a non‐invasive alternative to neurosurgery which uses radioactive cobalt sources to treat a variety of intracranial conditions ranging from tumours and metastases to functional disorders. It is a platform for stereotactic radiosurgery, a highly precise form of radiotherapy utilising very high doses to the target while maximally sparing surrounding normal brain. LGK enables patient planning and treatment to be done in one day as an outpatient procedure. This paper will outline our LGK service and provide insight into the expanded role that radiation therapists have within the multidisciplinary team required to deliver radiosurgery in a timely manner. The training programme and radiation licensing pathway that have been established for radiation therapists will also be described. Abstract : This paper will outline our Gamma Knife service and provide insight into the expanded role that radiation therapists have within the multidisciplinary team required to deliver radiosurgery in a timely manner. The training program and radiation licensing pathway that have been established for radiation therapists will also be described.